Breast cancer awareness in student nurses: Implications for health promotion - Heffernan, Claire (2011)
The purpose of this study was to explore student nurses‟ knowledge of breast cancer, and their ability and confidence to promote breast cancer awareness. The literature review highlighted that there has been a minimal amount of research published into this area, identifying the need for more contemporary research.